2023
DOI: 10.3390/biology12010083
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of Traumatic Head and Neck Injuries on Women: A State-of-the-Art Review and Future Directions

Abstract: The biomechanics of traumatic injuries of the human body as a consequence of road crashes, falling, contact sports, and military environments have been studied for decades. In particular, traumatic brain injury (TBI), the so-called “silent epidemic”, is the traumatic insult responsible for the greatest percentage of death and disability, justifying the relevance of this research topic. Despite its great importance, only recently have research groups started to seriously consider the sex differences regarding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 228 publications
(244 reference statements)
0
9
0
Order By: Relevance
“…Ligamentous laxity predisposes a joint to injury as it is inherently more unstable, and relies more on dynamic stabilizers (i.e., muscles) to prevent injury. A study performed by Carmo et al examining whiplash injury in motor vehicle collision showed that females had higher risk of concussion 22 . Although not sports related, this study suggests that the external forces combined with the female anatomy could lead to differing exposure to head injury than males.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Ligamentous laxity predisposes a joint to injury as it is inherently more unstable, and relies more on dynamic stabilizers (i.e., muscles) to prevent injury. A study performed by Carmo et al examining whiplash injury in motor vehicle collision showed that females had higher risk of concussion 22 . Although not sports related, this study suggests that the external forces combined with the female anatomy could lead to differing exposure to head injury than males.…”
Section: Discussionmentioning
confidence: 52%
“…Female vertebrae from C3–7 are significantly smaller than male vertebrae in the anterior-posterior dimension. Males also have more linear and areal dimensions of the cervical spine compared to females 22 . This could indicate males have a more stable spinal column that could resist inertial loads.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TBI affects individuals across a wide spectrum of demographics, but the specific risk factors, outcomes, and mechanisms of injury can vary significantly among different groups [ 3 , 4 ]. While TBI research has traditionally centered on general populations, there's a growing recognition of the necessity for tailored investigations, particularly in the context of unique subpopulations such as females [ [5] , [6] , [7] ]. It is now clear that TBI doesn't uniformly impact all individuals.…”
Section: Introductionmentioning
confidence: 99%